Policy, Participation and Empowerment: A Case Study of Community Resistance to Shells Seismic Blasting in the Eastern Cape - Tomaselli, Charlize (Department of Sociology, 2023)
This research examines the conflict in South African government policy between a people-centred participatory rhetoric on the one hand, and neoliberal growth-centred rhetoric on the other; and how this has played out in the recent series of related court cases. The methodology employed was a case study design based on the judgments in a series of related court cases (2021 – 2022) between local fisher communities of Dwesa Cebe, Port St. Johns and Kei River mouth in the Eastern Cape, South Africa; Sustaining the Wild Coast; and Natural Justice Attorneys versus Shell Corporation, Shellsubsidiaries and two South African Government ministers (Minerals, Petroleum and Energy, and Environment and Tourism). Thematic analysis was applied as the data analysis method. The conceptual framework utilised Jürgen Habermas' instrumental reasoning as a high-level framework and was operationalised through the heuristic modules of participation by Sherry Arnstein and Jules Pretty. The research makes the case that issues of public participation in this instance are a result of the different understandings and expectations of the required level of public participation between the opposing partiesin the series of court cases, namely the local fisher community1 and Shell Corporation together with Government. The claim is that this is largely a result of the conflicting and sometimes opposing policy rhetoric within government policy. I focus on conflicting elements within the National Environmental Management Act and the Mineral and Petroleum Resources Development Act in this case study. The findings underscore the central importance of appropriate levels of public participation, as protected by the South African Constitution, in the process of Exploration Right Applications in order to highlight conflict between different stakeholders.